Determinants of the relative price impact of unanticipated information in US macroeconomic releases - Dieter E. Hess (Hochschule für Bankwirtschaft (HfB), 2003)
This paper investigates the intraday response of T-bond futures prices to surprises in headline figures of U.S. macroeconomic reports. Analyzing the time series properties and the information content of the macroeconomic news flow, the paper seeks an answer to the question, what determines the relative price impact of releases. Several types of information regarding inflation and economic strength are distinguished and the explanatory power of the type of information is tested against the alternative hypothesis that the timeliness of a release determines its impact.
urn:nbn:de:101:1-2008072120
Keywords: E44; G14; G15; 330; Macroeconomic releases; information processing; T-bond futures